Characterizing Spectrum Goodness for Dynamic Spectrum Access - Chowdhery, Aakanksha; Chandra, Ranveer; Garnett, Paul; Mitchell, Paul (50th Allerton Conference on Communication, Control and Computing, 2012)
The combination of exclusive use spectrum licensing and growing demand for voice, data, and video applications is leading to artificial spectrum scarcity. A recent approach to alleviate this artificial spectrum scarcity innovatively uses unused TV spectrum, also called the TV white spaces, through dynamic spectrum access (DSA) techniques. Wireless devices can use DSA techniques such as sensing and geo-location databases to learn about available TV channels for wireless communication. One obvious question to ask is whether the technology enabler for white space networking, i.e. dynamic spectrum access, is viable in other portions of the spectrum? This paper extends our research on networking devices in TV white spaces over the last seven years to other licensed spectrum bands between 30 MHz and 6 GHz. Typically, the goodness of licensed spectrum bands is measured using spectrum occupancy as a goodness metric, but the DSA opportunities in different bands can depend on several factors. We propose a novel DSA goodness metric to compare the opportunity of capitalizing on available spectrum using DSA techniques in various licensed bands. Further, we use these metrics to evaluate the data from the ongoing spectrum measurement campaign at Microsoft Research over one year.